Desenvolvimento de materiais a base de quitina para aplicação na adsorção de corantes - Druzian, Susanne Pedroso (2021)
The environmental problems due to the accelerated industrialization of the last decades have caused in society the need to develop new technologies for the treatment of industrial waste. The textile industry stands out due to the high consumption of water in its production process and the large volumes of effluents generated containing contaminating compounds, such as dyes, with great potential for the pollution of water bodies. As result, an extensive research has been carried out to develop technologies for the treatment of effluents containing dyes, among which adsorption stands out for its low cost and high efficiency. Chitin is a biodegradable and renewable biopolymer that can be used as a basis for the development of adsorbent materials. In this context, the present work aimed to develop materials from chitin for application in the removal of crystal violet dye from aqueous solutions by adsorption. First, chitin was obtained from shrimp residues, and by acid hydrolysis of the obtained chitin, nanowhiskers were synthesized. Both materials were characterized and applied for adsorption studies. The characterization of the materials showed that the nanowhiskers had a rod shape and a larger average pore size when compared to chitin. The adsorption tests showed that the adsorption was favored using 5 g L-1 of nanowhiskers and solution with a pH of 8. The pseudo-second order model was the most adequate to represent the kinetic data and the Sips model the best represented the equilibrium curves. The process was endothermic, spontaneous and favorable. The maximum adsorption capacity of crystal violet was 59.52 mg g-1, which corroborated the potential of nanowhiskers to be used as an adsorbent in the treatment of colored effluents. A new aerogel was also synthesized from chitin. This aerogel was obtained by the freeze-drying of a gel of chitin and psyllium. The developed material was characterized and applied for adsorption studies. The characterization showed that the aerogel has a typical structure of amorphous materials with a porous and randomly interconnected structure that resembles an open pore network. The adsorption was favored using 2.5 g L-1 of aerogel and solutions with a pH of 8. The pseudo-second order and Freundlich models satisfactorily described the kinetic and equilibrium data, respectively. The maximum adsorption capacity of crystal violet was 227.11 mg g-1, which indicates that aerogel is very efficient and competitive with several other adsorbents described in the literature for removing crystal violet from aqueous solutions. Tests using aerogel to treat simulated textile effluents showed that this material has great potential to treat real colored effluents. In summary, it can be concluded that the development of adsorbents from chitin contributes strongly to research on the development of technologies for the treatment of effluents containing dyes.